Allosteric modulation of G protein-coupled receptor signaling - Shen, Siyuan; Zhao, Chang; Wu, Chao; Sun, Suyue; Li, Ziyan; Yan, Wei; Shao, Zhenhua (Frontiers in Endocrinology, 2023)
G protein-coupled receptors (GPCRs), the largest family of transmembrane proteins, regulate a wide array of physiological processes in response to extracellular signals. Although these receptors have proven to be the most successful class of drug targets, their complicated signal transduction pathways (including different effector G proteins and β-arrestins) and mediation by orthosteric ligands often cause difficulties for drug development, such as on- or off-target effects. Interestingly, identification of ligands that engage allosteric binding sites, which are different from classic orthosteric sites, can promote pathway-specific effects in cooperation with orthosteric ligands. Such pharmacological properties of allosteric modulators offer new strategies to design safer GPCR-targeted therapeutics for various diseases. Here, we explore recent structural studies of GPCRs bound to allosteric modulators. Our inspection of all GPCR families reveals recognition mechanisms of allosteric regulation. More importantly, this review highlights the diversity of allosteric sites and presents how allosteric modulators control specific GPCR pathways to provide opportunities for the development of new valuable agents.